The effectiveness of communication interdependence between teachers, parents, assessors, and entrepreneurs affecting the work and entrepreneurial skills of vocational high school students - Rosmawaty Hilderiah Pandjaitan; Elena Shinta Maharani Hutajulu (Jurnal Pendidikan Vokasi, 2021)
This research aims to describe the model, quantity percentage, and factors that affect the effectiveness of communication interdependence between teachers, parents, accessors, and entrepreneurs, affecting vocational high school students' work and entrepreneurial skills (SMKN 7 Tangerang Regency in Industrial Era 4.0). The data analysis method used in this study is used criterion-related validity test in the form of predictive validity, using product-moment correlation technique. This study is quantitative research with a survey method involving 372 respondents from SMKN 7 Tangerang. This study employed Mixing Theory System (Bertalanffy), Theory Open System (Shawn Fanning), and Social System  Theory (Nikias Luhmann). Test reliability was done by Cronbach's Alpha formula, SPSS 24, and Pearson's Correlation Test, "F" test, and "T" test. The results show that (1) many factors that affect the effectiveness of interdependence of educational communication at this school in the industrial era 4.0, including education knowledge, communication skills (multiple contingencies), communication behavior control (flexible and creative), and emotional communication (adaptable). (2) Only interdependence of communication between students and entrepreneurs is rated 100% effective towards work and entrepreneurial skills at SMKN 7 Tangerang students in the industrial era 4.0.